Shopaholic Lifestyle Phenomenon for College Students in Surakarta City - Solekha, Wahyu Isnaeni; Jatmika, Surya; Sari, Dhany Efita (Universitas Muhammadiyah Surakarta, 2023)
The shopaholic lifestyle is a form of consumptive behavior. Many students in the city of surakarta have a shopaholic lifestyle. The purpose of this research is to describe the lifestyle of shopaholic students in the city of surakarta and to identify factors that influence the lifestyle of shopaholic students in the city of surakarta. This is a qualitative study with a string of phenomena designs. The subject of this study is ten students studying in surakarta. The ten students consisted of two students from the muhammadiyah university of surakarta, two students from sebelas maret university, two students from the Indonesia institute of arts surakarta, two students from the Tunas Pembangunan university, and two students from the university of slamet riyadi. Data collection techniques included interviews, observation, and documentation. The data validity used source triangulation and technical triangulation. The data analysis technique used interactive analysis. The results of this study indicate that theshopaholic lifestyle of college students tends to spend money to shop compulsively with a fairly high frequency. Students of shopaholic have a life that is prone to luxury or hedonics that they indulge in involuntary and continual consumption without any consideration that causes students to become consumptive. The factors that influence students to become shopaholics are luxury lifestyle and hedonic lifestyle, influence from family, advertising, following trends, and lots of shopping centers.